Regional Dissection of the Human Female Pelvis - Alan J. Detton; Eric J. Kenz; Lisa M.J. Lee (Association of American Medical Colleges, 2012)
Abstract This resource is a concise supplementary laboratory dissection guide and review for regional gross anatomy of the human female pelvis. The resource is intended primarily for undergraduate and graduate medical students and residents who are performing pelvic dissections, preparing for their board examinations, or simply reviewing the gross anatomy of the female pelvis. The resource contains a cogent, 25-page PDF file on regional dissection of the human female pelvis created for use by faculty, students, and residents in medicine and allied health professions, with students and faculty in anatomy courses in mind. The PDF features images with and without labels to point out hard-to-dissect, complex, three-dimensional regions and structures of the human female pelvis. These structures are challenging to dissect in gross labs and are commonly observed in sagittal sections, making it difficult to evaluate three-dimensional anatomical structure and relationships. The framework provides a concise review of these challenging-to-identify structures for users during or after pelvic dissection and as a supplement to currently available atlases. Additionally, all original images and labels provided in the presentation may be adapted for use in a variety of educational settings to increase discussion and instructional efficiency and to foster a comprehensive review.